Analisis Proses Rekaman Musik dengan Metode Digital di Cover Studio - Herlina Kusumaningrum; Dewanto Sukistono (Journal of Music Science, Technology, and Industry, 2020)
Purpose: This study aims to describe the analysis of the process of recording music with digital methods in Cover Studio. Research methods: As stated in the title of this article, the method used in this research is a digital one. The recording is taken in Cover Studio, in Yogyakarta, Indonesia. Results and discussion: The recording process at Cover Studio consisted of the preplanning or preparation stages, data collection or tracking, mixing and mastering. Implication: Most of the recording work is done digitally such as making data keyboards using a midi controller with VST JJP Strings and Key and Xpand! 2, miking instruments or musical instruments using VST, drums using VST Addictive Drums 2.